Financial resilience of rural hospitals: Prepandemic vulnerabilities and Provider Relief Funds’ role during COVID‐19 - Karim, Saleema A.; Carroll, Nathan W.; Song, Paula H.; Atherly, Adam (The Journal of rural health, 2025)
Purpose Rural hospitals struggling with prepandemic financial instability faced heightened challenges during COVID‐19. While Provider Relief Funds (PRFs) offered essential support, their impact varied, highlighting the need to examine how prepandemic financial health influenced rural hospitals’ financial performance during the pandemic. This study evaluates PRF's role across three hospital categories: financially strained (low operating margin), financially vulnerable (midrange operating margin), and financially strong (high operating margin). Methods A cohort study with a pre–post research design analyzed 2243 US rural hospitals from 2017 to 2022. The sample included short‐term general acute nonfederal hospitals and Critical Access Hospitals in nonmetropolitan counties and rural tracts within metropolitan counties. Financial health was assessed using operating margin measures and total margins with and without PRF across four time periods: pre‐COVID‐19 (2017–2019), COVID‐19 Year 1 (2020), Year 2 (2021), and Year 3 (2022). Findings Financially strained and vulnerable hospitals represented 85% of rural hospitals. Financially strained hospitals had the lowest average operating margins from patient services (−17.36%), trailing financially vulnerable (−3.09%), and financially strong (8.04%). In COVID‐19 Year 1, operating margins declined across all categories. PRF increased total margins for financially strained hospitals to 8.39% in 2021 before dropping to 0.76% in 2022. Financially vulnerable hospitals also benefited, while financially strong hospitals remained profitable even without PRF. Conclusion PRF played a critical role in stabilizing rural hospitals, mitigating financial declines, and preventing closures. Its expiration leaves many hospitals facing renewed financial pressures. Addressing long‐term financial challenges through sustainable funding strategies and operational adaptations will be essential to preserving health care access in rural communities.